2021
DOI: 10.1097/pec.0000000000002455
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Septic Knee Monoarthritis Prediction Rule in a Lyme Disease Endemic Area

Abstract: In Lyme disease endemic areas, Lyme and septic arthritis often present similarly. A published septic knee arthritis clinical prediction rule includes 2 high-risk predictors: absolute neutrophil count of 10,000 cells/mm 3 or greater and erythrocyte sedimentation rate of 40 mm/h or greater. The objective of the study was to externally validate this prediction rule in a multicenter prospective cohort. Methods:We enrolled a prospective cohort of children with knee monoarthritis undergoing evaluation for Lyme disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…This is comparable to data obtained from the CDC, where the overall average age of patients with Lyme arthritis is reportedly between 10 and 14 years old. However, previous studies focusing on more rural endemic regions found the presenting age to be lower, with reported averages of 6.7 and 7 years [4,12,15].…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…This is comparable to data obtained from the CDC, where the overall average age of patients with Lyme arthritis is reportedly between 10 and 14 years old. However, previous studies focusing on more rural endemic regions found the presenting age to be lower, with reported averages of 6.7 and 7 years [4,12,15].…”
Section: Discussionmentioning
confidence: 96%
“…Small case series have reported 37.5% and 70% of patients with Lyme arthritis had surgical treatment [16,22]. A larger study comparing patients with Lyme to septic arthritis noted 12.4% of Lyme arthritis patients underwent an irrigation and debridement [12]. In a retrospective review of 149 patients comparing patients who underwent operative versus non-operative intervention for Lyme arthritis, Tout et al reported 32% of patients underwent operative intervention.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations